PENILAIAN KETERAMPILAN PORTOFOLIO DALAM PEMBELAJARAN - Hakim, Lukmanul; Ubabuddin, H (ILJ: Islamic Learning Journal, 2023)
Portfolio assessment is a continuous assessment method with various collections of information or documentation of one's work taken during the learning process within a certain period of time and stored in a bundle in a systematic and organized manner. This assessment is considered by some educational researchers to be an alternative assessment in the modern world and is much more reliable and valid than standard assessments. This research is a literature research, by collecting documentary data, and analyzed by content analysis. Modelportofolio assessment suitable for women lesson that     demandingoutput student learning in terms of knowledge, skills and attitudes. The aspects measured in the portfolio assessment are the three domains of child psychology development, namely cognitive, affective and psychomotor. The components of the portfolio assessment include: (1) teacher notes, (2) student work results, and (3) student development profiles. The function of portfolio assessment is as a tool to determine the progress of competencies that have been achieved by students and to diagnose students' learning difficulties, provide feedback for the benefit of improving and perfecting learning.